2019
DOI: 10.1007/s10096-019-03494-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness to prescribe antibiotics responsibly: a comparison between final year medical students in France and Sweden

Abstract: Students should graduate from medical school feeling prepared to prescribe antibiotics responsibly. We assessed self-reported preparedness among students at medical schools in Europe, and we focus here on the results from students in Sweden and France, countries with wide differences in the intensity of antibiotic consumption and burden of antibiotic resistance. We conducted a cross-sectional web-based survey in 2015, based on a comprehensive set of topics related to prudent antibiotic use. All final year stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 18 publications
3
19
0
1
Order By: Relevance
“…Possible explanations for these ndings include a difference in the quality of education provided in different countries, but also cultural factors related to self-con dence and preparedness feeling [6,11,17]. Cultural differences between French speaking and German speaking regions in Switzerland have been pointed out as one of the factors in uencing the disparities regarding use of antibiotics and rates of antimicrobial resistance among Swiss cantons [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible explanations for these ndings include a difference in the quality of education provided in different countries, but also cultural factors related to self-con dence and preparedness feeling [6,11,17]. Cultural differences between French speaking and German speaking regions in Switzerland have been pointed out as one of the factors in uencing the disparities regarding use of antibiotics and rates of antimicrobial resistance among Swiss cantons [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…This Student-PREPARE survey investigated self-reported preparedness on different topics about prudent antibiotic use and the perceived lack of education, and compared the results among the participating countries. Although some differences emerged across countries, most European students expressed a need for more education on antibiotic use [6,11,12]. In this manuscript we present an in-depth subgroup-analysis of the Swiss results of the survey.…”
Section: The Escmid (European Society Of Clinical Microbiology and Inmentioning
confidence: 98%
See 1 more Smart Citation
“…Likewise, another study found that French medical students demanded more educational training in prescribing than Swedish counterparts, and the final year French medical students' self-perceived readiness to prescribe an antibiotic after graduation was lower than their Swedish counterparts ( 312 ).…”
Section: Overcoming the Problemsmentioning
confidence: 99%
“…André Ricardo Araujo da Silva et al https://doi.org/10.1590/1981-5271v43suplemento1-20190084 que mensuraram a carga horária 7 . A despeito da variabilidade da carga horária destinada a este tema, é possível que haja necessidade de melhor capacitação dos futuros médicos, como demonstrado por Dyar et al 13 . Esses autores avaliaram 2.085 estudantes de escolas médicas do último ano da França e Suécia a respeito de autoanálise e confiança para prescrição de antibióticos e evidenciaram que pouco mais de 63,5% dos estudantes franceses e 20,3% dos estudantes suecos consideraram a necessidade de receber mais informações sobre o uso de antibióticos.…”
unclassified